Controllability of Systems with a General Nonlocal Condition - Henriquez-Miranda, H (Academic Press, 2020)
In this work we are concerned with the controllability of first order distributed systems with a general nonlocal condition. Specifically, by a general nonlocal condition we understand a nonlocal condition modeled in terms of an inclusion. In this context, assuming that the underlying linear system is approximately controllable, we present three types of conditions under which the nonlinear system is also approximately controllable. © 2020 Elsevier Inc.